PENGARUH BUDAYA PERUSAHAAN DAN KOMITMEN PERUSAHAAN TERHADAP INTENSITAS PERAN AKUNTANSI MANAJEMEN - Yayuk Nurjanah; J. Sumarno (Media Riset Akuntansi, Auditing & Informasi, 2010)
The goals of the research are to find out and to analyze: (1) the influence of the company culture on the intensity of the management of accountancy role, (2) the influence of the company commitment on the intensity role of the management of accountancy, and (3) the influence of the culture and commitment of the company on the intensity of the management of accountancy role. The type of this research is hypothesis analysis research. And the objects of the research are the managers of the manufacture companies in Bogor. The method used for collecting the data is the one in which 100 questionnaires were delivered to the managers. Of 52% of the questionnaires returned, only 45% of it was qualified to be processed. The hypothesis, classical assumption and the quality of data are processed statistically. The results of the analyses are that (1) the culture of the company shows significant influence on the intensity of management of accountancy, (2) the commitment of the company also shows significant influence on the intensity of the management  of accountancy, and (3) the culture and the commitment of the company show significant influence simultaneously on the intensity of the management of accountancy role. The conclusion of this research shows the same conclusion as performed by Eka Priastana Putra and Ainun Naim(2000) and M. Laras W. (2005) at the same case.